Region insurance sector to proceed carefully to guarantee an advantageous position in the global community - Lawson, Sheron (2004)
Provides a synopsis of the report on the FTAA Stakeholders Working Summit held on March 26, 2004 in Barbados. Looks at areas of consensus and highlights major concerns such as the weak regulatory condition in some countries, as well as the slow implementation of the Caribbean Single Market and Economy. Seeks to formulate a position for the FTAA negotiations that is reflective of the Caribbean insurance industry.